Pictorial and affective crossings in A escuridão, o corpo vermelho e o fascínio (Orfeu, 2020)
This article brings a repport of a musical compositional process which had a painting by the visual artist Tomie Ohtake as source of materials and poetic ideias. We will discuss different aspects of the compositional activity, so that the writing tools, the definition of formal aspects and the poetic potencials will be ilustrated. Besides that, some influencies from other sources connected to the context of the composition will be commented. This way we seek to demonstrate a possibility of work to deal with the problematic of creating music from a visual work.
Keywords: Creative processes; artistic crossings; compositional tools; music and painting